Structure of financial institutions - Bhatt, V. V. (Bombay : Vora, 1972)
The papers in this book are concerned with the policies and the policy instruments that are essential to enable the financial system to assume the role of initiating the process of development
Includes bibliographical references.
osc 28/9/17
Loans
Keywords: Financial institutions; Finance; India